Bioavailability enhancement of acyclovir by honey: Analytical and histological evidence - Mady, Omar Y.; Osman, Mohamed A.; Sarhan, Naglaa I.; Shatla, Ali A.; Haggag, Yusuf A. (Journal of drug delivery science and technology, 2023)
Acyclovir is a BCS class III drug that has high solubility and low permeability. Acyclovir is an antiviral drug used for the treatment of herpes simplex and varicose zoster. d-glucose is reported as a permeation enhancer for BCS class III drugs. It is the most commonly occurring isomer of glucose in nature. Honey is one of the public foods. Therefore, it was tried to study the enhancement of honey on the absorption of acyclovir in vivo in comparison with pure d-glucose. The effect was studied in albino rabbits using a 2-way parallel pharmacokinetic study from a hypo-osmotic solution containing the drug with different additives. The order of bioavailability enhancement of the additives to the drug can be arranged according to the following: honey (10.09 folds) > d-glucose-NaCl (8.33 folds)> honey-NaCl (7.77folds) > d-glucose (5.63 folds). d-glucose has been transported actively through the transcellular pathway (SGLT1) producing energy that led to a contraction of the prejunctional actomyosin ring resulting in the widening of the paracellular pathway. More widening of the paracellular pathway could be expected by using honey as a result of its content of glucose, fructose, and sucrose. The winding effect of the additives was histologically studied using light staining and a transmission microscope. d-glucose showed very thin tight junctions between closely adjacent enterocytes while d-glucose with NaCl revealed several enterocytes with one widely dilated tight junction and loosening and thinning of the others. Honey treated group demonstrated loosening and wide dilatation of the tight junctions. The analytical and histological evidence support the bioavailability enhancement of d-glucose to the drug which will be more pronounced from food sources. [Display omitted]